Surface characteristics and bioactivity of titanium preserved in a baicalin-containing saline solution - Liu, Yao; Yang, Yue-hua; Liu, Xu; Xiao, Yu; Bao, Chong-yun; Wang, Xiao-song (Frontiers in Materials, 2025)
ObjectiveThis study aimed to develop a baicalin (BA)-containing storage saline solution and investigate their effects on the physicochemical properties and bioactivity of sandblasted with large grit and acid-etched (SLA) titanium surfaces.Materials and methodsSLA titanium specimens stored in air and 0.9% NaCl solution were served as controls and stored in three different concentrations of baicalin-containing saline solution were served as experimental groups to investigate the effects of the new storage methods. The specimens were examined for surface microstructure, surface element composition, surface wettability and roughness by field emission scanning electron microscopy, X-ray photoelectron spectroscopy (XPS), water contact angle measurement and laser confocal microscopy, respectively. In addition, the osteoblasts proliferation assay was used to investigate the bioactivity of the SLA titanium surfaces preserved in different conditions.ResultsThe micron-scale crystals of different diameters were observed on surfaces stored in three different concentrations of baicalin-containing saline solution. XPS analyses revealed that the amount of titanium dioxide (TiO2) decreased and the carbon (C) increased with the concentration of baicalin increasing. Compared to the control groups, specimens stored in baicalin-containing saline solution exhibited better hydrophilicity. The roughness results showed that specimens stored in 10 µM BA and 100 µM BA solutions displayed lower surface roughness. Moreover, the preservation of specimens in the 100 µM BA solution greatly enhanced the proliferation of osteoblasts.ConclusionThe storage of SLA titanium materials in baicalin-containing saline solution, especially in the concentration of 100 µM baicalin, could effectively improve the surface properties and make the environment conducive to the proliferation of osteoblasts, which could be a new type of titanium implant storage solution.